DNA barcoding and eDNA barcoding in diatoms - Zimmermann, Jonas; Justus Liebig University Giessen (My University, 2014)
The microscopical analysis of diatom diversity is a well established approach in the assessment of the ecological status of water bodies and implemented e.g. in the European Water Framework Directive. This dissertation presents environmental DNA (eDNA) barcoding of diatom communities as an alternative methodology to the routine use of light microscopy.The V4 locus of the 18S rRNA gene is introduced in this work as an adequate DNA barcoding marker for diatoms: the locus is flanked by regions that are conserved throughout the diatoms, thus serving as universal primer binding sites. The 18S V4 region also contains sufficient sequence variation for diatom discrimination on a stretch of only approximately 390 bp; therefore it is also suitable for next generation sequencing. A standard laboratory protocol for the amplification of this marker from diatoms in culture as well as from environmental samples is specified in the present dissertation. Furthermore, this work includes the agreement of the CBOL Protist Working Group (ProWG) on the 18S V4 locus as pre ]barcode for the assessment of general protist diversity. In addition to that each protist group could apply a second marker region to further examine taxon delimitation and diversity, if necessary.eDNA barcoding relates unidentified sequences from an environmental sample to identified sequences in a reference database to obtain an assignment of the environmental sequences to a respective taxon. The present study investigates the taxonomic discriminatory power of eDNA barcoding in comparison to light microscopy. It is demonstrated that the DNA based approach provides a more refined taxon detection than the microscopical approach. As the simple BLAST algorithm proved to be insufficient for the assignment of sequences to taxonomic entities, the phylogenetic ]based coalescent model approach (PCMA) is introduced. The PCMA combines the general mixed Yule ]coalescent (GMYC) model . a tree based approach ] with the statistic evaluation of genetic clusters via bootstrap support.It is also shown that the quality of sequence assignment to taxonomic entities is directly related to the quality of the taxonomic treatment of the reference sequences; and the information in the most commonly used reference database INSDC (International Nucleotide Sequence Database Collaboration; incl. Genbank, EMBL/ENA and DDBJ) is of questionable quality.This work therefore includes best practice guidelines for the deposition of sequence information in taxonomic reference libraries. In diatoms reference sequences are almost always obtained from clonal cultures permitting good documentation possibilities. Along with the reference sequences, physical vouchers in form of herbarium specimen and the DNA extract need to be deposited in scientifically curated collections. Also minimum requirements for metadata are suggested: these include e.g. collection data, cultivation data, primer and amplification details, pherograms, as well as photographic documentation of microstructures important for identification. Even though these specifications are proposed for diatoms, they are transferable to other protist groups and also beyond that. As parts of the specified metadata cannot be deposited in the INSDC along with the sequence data, AlgaTerra and the database of the DNA Bank Network are discussed as complements.The publications assembled in the present dissertation contribute towards the establishment of the standard application of eDNA barcoding in water quality assessments via diatom community analysis by introducing (a) a methodological approach and (b) best practice guidelines for the deposition of reference sequences.

Die lichtmikroskopische Bewertung der Diversität von Diatomeen ist eine erfolgreich praktizierte Methode zur Gewässergüteanalyse, die z.B. auch in der Wasserrahmenrichtlinie der Europäischen Union umgesetzt wird. Die vorliegende Arbeit stellt environmental DNA (eDNA) Barcoding als Alternative zur üblichen Untersuchung von Diatomeengesellschaften mit Hilfe von Lichtmikroskopie vor.Die auf dem 18S rRNA Gen befindliche V4 Region wird in dieser Dissertation als adäquater Marker für Diatomeen DNA Barcoding eingeführt: die Region wird von innerhalb der Diatomeen konservierten Sequenzabschnitten flankiert, die als universelle Primer-Bindungsstellen fungieren können. Des Weiteren zeigt die 18S V4 Region auf einem relativ kurzen Sequenzabschnitt (ca. 390 bp) ausreichend Variation für die Unterscheidung verschiedener Taxa. Die geringe Abschnittslänge ermöglicht zusätzlich die Sequenzierung durch Next-Generation-Sequencing-Technologie. Die Arbeit beinhaltet ein Standardprotokoll für die Amplifizierung der 18S V4 Region sowohl aus Kulturmaterial als auch aus Umweltproben. Außerdem ist in der vorliegenden Studie die Entscheidung der CBOL Protist Working Group (ProWG) für die 18S V4 Region als Pre-Barcode für alle Gruppen der Protisten enthalten. Der Marker wird also zur generellen Erfassung der Protistendiversität vorgeschlagen. Sollte darüber hinaus ein weiterer genetischer Marker für die Untersuchung von Taxongrenzen und Diversität innerhalb einzelner Gruppen nötig werden, wird dieser für jede Protistengruppe einzeln festgelegt.Beim eDNA Barcoding werden unidentifizierte Sequenzen aus einer Umweltprobe identifizierten Sequenzen in einer Referenzdatenbank zugeordnet, um die Sequenzen aus der Umweltprobe einem entsprechenden Taxon zuzuweisen. Die hier vorgestellte Untersuchung prüft die Unterschiede von Lichtmikroskopie und eDNA Barcoding hinsichtlich ihrer Möglichkeiten der taxonomischen Unterscheidung. Die sequenzbasierte Methodik lieferte eine feinere taxonomische Aufgliederung als die Lichtmikroskopie. Da sich eine einfache Zuordnung von Sequenzen zu taxonomischen Einheiten mittels des BLAST Algorithmus als nicht ausreichend erwies, stellt diese Arbeit den phylogenetic-based coalescent model Ansatz (PCMA) vor. Dieser kombiniert das general mixed Yule-coalescent (GMYC) Modell, einen auf Baumberechnungen beruhenden Ansatz, mit der statistischen Unterstützung einzelner genetischer Gruppen durch den Bootstrap Support. Zusätzlich wird der direkte Zusammenhang von der Qualität der Sequenzzuordnung zu taxonomischen Einheiten zur Qualität der taxonomischen Bearbeitung von Referenzsequenz gezeigt. In der gebräuchlichsten Referenzdatenbank INSDC (International Nucleotide Sequence Database Collaboration; inkl. Genbank, EMBL/ENA and DDBJ) ist die vorhandene taxonomische Information zu Diatomeensequenzen fragwürdig.Deshalb schlägt die vorliegende Arbeit Richtlinien zur Hinterlegung von Referenzsequenzen in taxonomischen Referenzdatenbanken vor. Referenzsequenzen werden im Falle der Diatomeen meist aus klonalen Kulturen erzeugt. Hierdurch ist eine umfangreiche Dokumentation möglich. Neben der Sequenzinformation sollten Herbarbelege und die physische DNA-Probe in wissenschaftlich betreuten Sammlungen hinterlegt werden. Minimalanforderungen für begleitende Metadaten werden ebenfalls vorgestellt; hierzu gehören neben Sammlungsdaten, Daten zur Kultivierung, Information zu Primern und PCR sowie den Pherogrammen auch die fotografische Dokumentation zur Bestimmung relevanter Mikrostrukturen. Diese Richtlinien für Diatomeen können ohne weiteres in anderen Protistengruppen oder auch darüber hinaus angewandt werden. Da ein Teil der aufgeführten Metadaten in INSDC nicht hinterlegt werden können, werden AlgaTerra und die Datenbank des DNA-Bank-Netzwerks ergänzend vorgeschlagen.Die in der vorliegenden Dissertation zusammengefassten Arbeiten tragen zur Etablierung von eDNA Barcoding als Standardanwendung zur Gewässergüteanalyse mittels der Untersuchung von Diatomeengesellschaften bei. Sie stellen erstens einen methodischen Ansatz vor und zweitens formulieren sie Richtlinien zur guten wissenschaftlichen Praxis hinsichtlich der Hinterlegung von Referenzsequenzen.
DNA Barcoding und eDNA Barcoding bei Diatomeen
Keywords: DNA Barcoding; Metabarcoding; Diatomeen; Gewässermonitoring; DNA barcoding; metabarcoding; diatoms; watermonitoring; ddc:570